Violence against women in the workplace: a narrative review (Brazilian Journal of Health Research, 2025)
Introduction: Violence against women in the workplace is a multifaceted phenomenon that reflects structural gender inequalities, mainly manifesting as moral harassment, sexual harassment, and discrimination. Objectives: To analyze the national scientific production published between 2016 and 2025 on violence against women in the workplace, identifying the main manifestations, impacts, and coping strategies. Methods: A narrative review was conducted, including 14 articles selected from databases such as BVS, SciELO, Google Scholar, and CAPES Journals Portal, using the descriptors "violence against women," "workplace violence," and "moral harassment." Results: The data indicated that harassment is the most prevalent form of gender-based violence in the workplace, impacting the mental and physical health of victims and generating significant social and organizational costs. Additionally, underreporting of cases and challenges in implementing effective public policies and organizational strategies were highlighted. Conclusion: Although Brazil has made progress in legislative frameworks, there are still significant gaps in the practical application of these policies, especially within organizations. Preventive strategies such as training, awareness campaigns, and reporting mechanisms are essential to transform organizational culture and promote gender equity in the workplace.
Keywords: Violence against women; Workplace violence; Moral harassment; Gender discrimination